New bis-pyrazolate zinc(ii) complexes as potential anticancer drugs: from structure to anticancer activity - Hasić, Rušid; Serezlić, Majda Kolenović; Caković, Angelina; Bogojeski, Jovana; Nikodijević, Danijela; Milutinović, Milena; Stanojević, Aleksandra; Čavić, Milena; Egorov, Andrei V.; Komolkin, Andrei V.; Kornyakov, Ilya V.; Scheurer, Andreas; et al. (New Journal of Chemistry, 2025)
Three novel Zn(ii) complexes [ZnCl2(H2LtBu)], [ZnCl2(Me2LtBu)] and [Zn2Cl4(H2LCatBiPyPh)2] (where H2LtBu is 2,6-bis(5-tert-butyl-1H-pyrazol-3-yl)pyridine, Me2LtBu is 2,6-bis(5-tert-butyl-1-methyl-1H-pyrazol-3-yl)pyridine and H2LCatBiPyrPh is 1,2-bis((5-phenyl-1H-pyrazol-3-yl)methoxy)benzene) were synthesized and characterized using various spectroscopic techniques, including UV-vis, IR, 1D (1H and 13C) and 2D (1H-1H COSY) NMR. The structures of complexes [ZnCl2(H2LtBu)] and [Zn2Cl4(H2LCatBiPyPh)2] were elucidated through X-ray crystallography. The interactions of the complexes with CT-DNA and human serum albumin (HSA) were investigated using UV-vis spectroscopy and fluorescence emission titration. All examined complexes exhibited quenching constant, Ksv, values in the order of 104 with CT-DNA. Constant values followed the trend [ZnCl2(Me2LtBu)] < [Zn2Cl4(H2LCatBiPyPh)2] < [ZnCl2(H2LtBu)]. The results indicated a moderate interaction between the complexes and HSA. In terms of cytotoxic activity, the zinc(ii) complexes significantly decreased the viability of colon (HCT-116) and pancreatic (MIA PaCa-2) cancer cell lines, where the effect on pancreatic cells after 72 h is especially emphasized. The most pronounced occurrence of apoptosis, as the dominant type of complex-induced cell death, was associated with complex [ZnCl2(H2LtBu)], while necrosis was observed at lower percentages in all investigated treatments. All complexes demonstrated downregulation of the tumor suppressor gene TP53 (homo sapiens tumor protein p53). Treatment with [ZnCl2(H2LtBu)] resulted in downregulation of TP53, CASP3 (Caspase 3) and IGF1R (insulin-like growth factor 1), potentially impairing the effective apoptotic process and reducing cell proliferation.
CRIS-Team Scopus Importer:2025-02-17